Prediction of protein structure from ideal forms - Taylor, William R.; Bartlett, Gail J.; Chelliah, Vijayalakshmi; Klose, Daniel; Lin, Kuang; Sheldon, Tom; Jonassen, Inge (Proteins, structure, function, and bioinformatics, 2008)
For many years it has been accepted that the sequence of a protein can specify its three‐dimensional structure. However, there has been limited progress in explaining how the sequence dictates its fold and no attempt to do this computationally without the use of specific structural data has ever succeeded for any protein larger than 100 residues. We describe a method that can predict complex folds up to almost 200 residues using only basic principles that do not include any elements of sequence homology. The method does not simulate the folding chain but generates many thousands of models based on an idealized representation of structure. Each rough model is scored and the best are refined. On a set of five proteins, the correct fold score well and when tested on a set of larger proteins, the correct fold was ranked highest for some proteins more than 150 residues, with others being close topological variants. All other methods that approach this level of success rely on the use of templates or fragments of known structures. Our method is unique in using a database of ideal models based on general packing rules that, in spirit, is closer to an ab initio approach. Proteins 2008. © 2008 Wiley‐Liss, Inc.